On Legal Consciousness: Based on a Critical Analysis of Legal Literature - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2022)
This article is devoted to the classification of legal consciousness, which is based on a critical analysis of modern legal literature. The paper provides a reasoned author’s view of the specified theoretical problem.